1985
DOI: 10.1037/0021-9010.70.2.401
|View full text |Cite
|
Sign up to set email alerts
|

Eyewitness memory enhancement in the police interview: Cognitive retrieval mnemonics versus hypnosis.

Abstract: This research compared the effectiveness of three interview procedures for optimizing eyewitness memory performance: (a) the "cognitive interview" based on memory-retrieval mnemonics from current memory theory, (b) the presently controversial hypnosis interview, and (c) the standard (control) police interview. These methods were evaluated empirically in a controlled, yet ecologically valid, laboratory setting. Eighty-nine subjects viewed police training films of simulated violent crimes and were questioned ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
235
3
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(252 citation statements)
references
References 46 publications
11
235
3
3
Order By: Relevance
“…Three similar studies (Ascherman, Mantwill, & Koehnken, 1991;Geiselman, Fisher, MacKinnon, & Holland, 1986b;Geiselman, Fisher, Mackinnon, & Holland, 1985) replicated the findings of Geiselman et al (1984 Geiselman et al (1985) also found that even when only critical facts, and not just total facts, were investigated the CI still elicited significantly more correct facts than the standard interview, without eliciting significantly more incorrect facts.…”
Section: Performance Measures For Cognitive and Standardsupporting
confidence: 68%
“…Three similar studies (Ascherman, Mantwill, & Koehnken, 1991;Geiselman, Fisher, MacKinnon, & Holland, 1986b;Geiselman, Fisher, Mackinnon, & Holland, 1985) replicated the findings of Geiselman et al (1984 Geiselman et al (1985) also found that even when only critical facts, and not just total facts, were investigated the CI still elicited significantly more correct facts than the standard interview, without eliciting significantly more incorrect facts.…”
Section: Performance Measures For Cognitive and Standardsupporting
confidence: 68%
“…Whereas in peripheral information there is a balance between the recall of actions and details, central information is represented basically by actions to the detriment of more particular details, a pattern which is even more marked in the intentional group. One might think that the subjects reconstructed the event by recalling typical actions of the kidnapping script, which would generate errors; however, as in previous studies (Geiselman et al, 1985;Sanders and Chiu, 1988;Yuille and Cutshall, 1986), there were very few errors in central actions.…”
Section: Discussionmentioning
confidence: 67%
“…Mental context reinstatement has also been studied as a key component of the CI that was developed in the early 1980s in an attempt to improve the quality of police interviews with adult witnesses (Geiselman et al, 1984). The primary aims were to increase both the quantity and the quality of information elicited from cooperative witnesses, victims, and suspects (Geiselman et al, 1984;Geiselman, Fisher, MacKinnon, & Holland, 1985. Since then, the CI has been modified for field settings as well as for children.…”
Section: Probing Memorymentioning
confidence: 99%